Behavior of concrete and mortar in response to the inclusion of toxic Jatropha seed cake - Santana, Marcelo [UNESP]; de Albuquerque, Maria da Consolação Fonseca [UNESP]; Isique, William Deodato [UNESP]; Pereira, Thiago Pastre [UNESP]; Gonçalves, Aparecido Carlos [UNESP]; Junior, Enes Furlani [UNESP]; Costa, Carla Neves (BioResources, 2018)
As the world's leading civil construction materials, concrete and mortar are the focus of ongoing studies aimed at improving their properties. These materials are highly versatile; hence, some of their aspects, such as their interaction with toxic materials, should be examined in greater depth. An investigation was therefore undertaken to ascertain how these products react to phorbol ester (PE), a toxin found in Jatropha seed cake (JSC). The mechanical behavior of mortar and concrete containing JSC waste from the manufacture of biofuel was examined based on the analysis of axial compressive strength. The interaction between mortar and PE molecules was examined by means of high performance liquid chromatography. A study of the mechanical behavior of the materials indicated that the inclusion of JSC greatly reduced their mechanical properties, and that this inclusion had a stronger impact on mortar than on concrete, while liquid chromatography showed that the toxic material inserted into the mortar remained inert, indicating the promising potential of this material to store toxic products.
Keywords: Concrete; Sustainability; Toxic material recycling